Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.physbeh.2011.12.026
|View full text |Cite
|
Sign up to set email alerts
|

The neurobiology of binge-like ethanol drinking: Evidence from rodent models

Abstract: Binge alcohol (ethanol) drinking is a destructive pattern of ethanol consumption that may precipitate ethanol dependence, a chronic, debilitating, and prevalent health problem. While an abundance of research has focused on the neurochemical underpinnings of ethanol dependence, relatively little is known about the mechanisms underlying the heavy consumption characteristic of binge ethanol drinking. Recently, a simple preclinical model termed “drinking in the dark” (DID) was developed to examine binge-like ethan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 70 publications
3
67
0
1
Order By: Relevance
“…Because rodents are nocturnally active, the drinking-in-the-dark (DID) model is used to examine binge-like ethanol consumption during periods of darkness. [33][34][35] EtOH conditioning in the dark chamber leads to arousal effects in mice and influences the rewarding effects of EtOH, as seen in the present study.…”
Section: Discussionsupporting
confidence: 73%
“…Because rodents are nocturnally active, the drinking-in-the-dark (DID) model is used to examine binge-like ethanol consumption during periods of darkness. [33][34][35] EtOH conditioning in the dark chamber leads to arousal effects in mice and influences the rewarding effects of EtOH, as seen in the present study.…”
Section: Discussionsupporting
confidence: 73%
“…Kong et al [2010] found that blocking the activity of these neurons in D. melanogaster attenuated the stimulant response to ethanol, and that the attenuated stimulant response to ethanol in flies lacking a D1-like dopamine receptor could be rescued by selective expression of the receptor in the ellipsoid body. These findings are consistent with a well-established role for dopamine in mediating ethanol-related behaviors in rodents and flies [Crabbe et al, 2006;Phillips and Shen, 1996;Scholz, 2009;Sprow and Thiele, 2012], which is in turn consistent with the model of Strausfeld and Hirth [2013] of conserved locomotorgenerating circuitry in arthropods and vertebrates.…”
Section: P O C C I D E N T a L I S M D I G I T A T A B G E R Msupporting
confidence: 89%
“…This drinking pattern has been shown to produce cognitive deficits and motivational alterations following repeated alcohol exposure (Bechara et al, 2001;Harper and Matsumoto, 2005;Stephens and Duka, 2008;Sprow and Thiele, 2012;Cippitelli et al, 2014;Townshend et al, 2014). The combination of alcoholic beverages and energy drinks (EDs) has been suggested to favor binge drinking because of increased palatability (e.g., the sweet taste) and the common misconception that EDs antagonize the depressant effects of alcohol.…”
Section: Introductionmentioning
confidence: 99%